Motivasi Kerja Perawat di ICU/ICCU dan HCU Rumah Sakit Dustira Kota Cimahi - Oyoh, Oyoh; Lilis, Lilis; Ardelia, Indrastata; Pragholapati, Andria (NHM PRESS, 2020)
Motivation can be interpreted as an internal push and to the extreme of the self in one person. Work motivation is an influential condition for arousing, directing, and maintaining behavior related to the work environment including nurse work motivation. This study aims to determine the description of the work motivation of nurses in ICU / ICCU and HCU inpatients at Tk II Hospital 03.05.01 Dustira Cimahi City in 2019. The study design was an analytic survey. The number of samples was 49 respondents using purposive sampling technique with inclusion and exclusion criteria. Data collection was performed using a Likert scale questionnaire method. Univariate data analysis to see the frequency distribution. The results showed as many as 26 respondents (53.1%) had high work motivation. It is recommended that the hospital continue to evaluate the work motivation of employees that have been done and increase employee job satisfaction, especially nurses are expected to further increase work motivation.